EFEKTIVITAS PENERAPAN PRINSIP-PRINSIP KEPEMIMPINAN KEPALA SEKOLAH TERHADAP PENINGKATAN MUTU LAYANAN ADMINISTRASI PENDIDIKAN - Suarga, Suarga (Idaarah: Jurnal Manajemen Pendidikan, 2017)
Globalization in the world of education is increasingly stronger demands on the quality of education. Quality education demands creative, innovative and productive individuals that can be said that only nations with quality education can compete globally. Educational services as a category of service (service) implemented by the institution of education or educational unit for and for the benefit of the community. Education should be oriented on improving the quality of services to create a fun and satisfying educational process that encourages learners to the spirit of learning which ultimately is expected to produce quality educational output. Service is a process of providing services (service delivery) from producers to customers (costumer). Quality services are services that meet or exceed the needs that service users expect. Activities to manage resources to support quality educational processes require professional, organized and planned educational management or administration. Therefore, the leadership role of the principal is very important. Leadership of principals is one of the determinants of the success of a school. Therefore, the principal must understand the roles and responsibilities it carries. According to Wahjosumijo there are two important roles of the principal, namely the principal acts as a central force that becomes the driving force of social life and the principal must understand his duties and functions for the success of the school, and has a concern for staff and students